The Prevalence and Structure of Arterial Hypertension and the Role of Apolipoproteins in its Development - Kadomtseva L.V.1, Babadjanov A.S.2, Pulatova S.Sh.3, Polikarpova N.V.4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The analysis of the inspection of the employees of Uzagrotehmash JSC was performed. A total of 1495 peopleaged 25-75 years have been examined (average age 46.3±0.3 years). The frequency of hypertension was 598people. High blood pressure was recorded more often in women (25.9%) than in men (16%), hypertensionis much more common at the age of 44-60 years and older, and hypertension has been found to be commonin overweight people (31, 6%), a large proportion was found in the structure of hypertensive patients withhypodynamia (50.2%). Among the protesters, 26.9% of people know about high blood pressure, but do nottreat it, and in 20.0%, high blood pressure was detected for the first time. The role of serum lipoproteins inthe hypertension development was confirmed, which allows patients to be assigned to a high-risk group forthe formation of cardiovascular diseases in subsequent life periods.